Pengaruh Modal, Tingkat Upah Dan Teknologi Terhadap Penyerapan Tenaga Kerja Dan Output Pada Industri Tekstil Di Kabupaten Badung - Harsinta Dewi, Anak Agung Yuli; Marhaeni, A.A. I.N (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 10, Oktober 2016 (pp. 1011 - 1167), 2016)
The purpose of this study was to analyze 1) Effect of capital, wages and technology on employment, 2) Effect of capital, wages, technology and employment to output, 3) The indirect effect of capital, wages and technology on output through employment. This research was conducted in Badung with respondents textile industry entrepreneurs covering 6 Subdistrict namely Abiansemal, Kuta, North Kuta, South Kuta, Mengwi and Evening. Object in this research include the capital, wages, technology, employment and output. Samples in this study amounted to 65 respondents. The sampling technique used is Proporsionate Stratified Random Sampling. Data collection methods used in this study include observation, interviews and in-depth interviews. Data analysis technique used is path analysis, path analysis and Sobel test to analyze the indirect influence through an intervening variable. The results showed capital, wages and technology and significant positive effect on employment of the textile industry .
Keywords: Capital, Wage Rates, Technology, Labor Absorption, Output